2011
DOI: 10.1111/j.1754-9485.2011.02316.x
|View full text |Cite
|
Sign up to set email alerts
|

Faculty of Radiation Oncology 2010 workforce survey

Abstract: There are a relatively large and increasing number of radiation oncologists and trainees compared with previous years. The excessive workloads evident in previous surveys appear to have diminished. However, further work is required on assessing the impact of ongoing feminisation and sub-specialisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 2 publications
0
44
1
Order By: Relevance
“…The trainee part of the census has revealed remarkable similarities to the 2014 census . Trainee numbers have stabilised, with 140 in this census compared to 142 in 2014 and 143 in 2010 . There was concern that numbers may drop because of concerns of oversupply in the workforce but, as mentioned previously, over 90% of recent graduates are finding employment .…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The trainee part of the census has revealed remarkable similarities to the 2014 census . Trainee numbers have stabilised, with 140 in this census compared to 142 in 2014 and 143 in 2010 . There was concern that numbers may drop because of concerns of oversupply in the workforce but, as mentioned previously, over 90% of recent graduates are finding employment .…”
Section: Discussionmentioning
confidence: 69%
“…However, a recent study has revealed over 90% of recent graduates in ANZ and Singapore were employed with over half of them employed as consultants . All three censuses this century have also revealed low unemployment amongst radiation oncologists in general with 1.3% unemployed in this census compared to 1.5% in 2014 and 2.6% in 2010 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Workforce issues that have been identified to increase ROs' stress include: increasing patient numbers, waiting lists and demands on time, limited opportunities for continuing professional development, perceptions that workforce is undervalued, and interpersonal/teaching demands (Leung, Rioseco, & Munro, 2014;Leung & Vukolova, 2011). Workforce issues that have been identified to increase ROs' stress include: increasing patient numbers, waiting lists and demands on time, limited opportunities for continuing professional development, perceptions that workforce is undervalued, and interpersonal/teaching demands (Leung, Rioseco, & Munro, 2014;Leung & Vukolova, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Faculty of Radiation Oncology (FRO) undertook the fifth workforce survey of radiation oncologists and trainees across Australia and New Zealand in 2014. The previous surveys were undertaken in 1996, 2000, 2006 and 2010 . The purpose of the 2010 survey was to create a faculty workforce database that could be updated regularly to analyse workforce trends and to create workforce models to predict future staffing and training requirements .…”
Section: Introductionmentioning
confidence: 99%